포장(PET/EVOH Film) 멸치조미가공품의 유통기한 예측 - 이의석(Eui-Seok Lee); 이형주(Hyong-Ju Lee); 배재석(Jae-Seok Bae); 김용국(Yong-Kuk Kim); 이종혁(Jong-Hyeouk Lee); 홍순택(Soon-Taek Hong) (東아시아食生活學會誌, 2013)
An attempt is made to predict the shelf life of seasoned anchovies packaged with laminated film, composed of polyethylene terephthalate (PET) and ethylene vinyl alcohol (EVOH). First, a descriptive sensory analysis is carried out to determine the principal sensory quality index in seasoned anchovies. Then, the physicochemical quality index with high correlation to the principal sensory quality index is determined accordingly. Subsequently, with the physicochemical quality index, the shelf-life is estimated by using the Arrhenius equation. As for the sensory quality index, 'color' is determined as a principal sensory quality index. For all samples stored at 3 different temperatures (25, 35, $45^{°}C$), it is observed that the sensory score is shown to be over 2.5 until 60 days of storage period, which is the lowest acceptable level. In addition, the b-value, as a physicochemical quality index, is determined to have a high correlation to the sensory quality index. Further, the activation energy and the Q10 value for the b-value by the Arrhenius equation is found to be 11.24 kcal/mol, 1.385~2.011, respectively. Thus, it can be concluded that the shelf life of seasoned anchovies packaged with PET/EVOH film is estimated to be 279.44 days when stored at $20^{°}C$.